MENUNJANG PEREKONOMIAN MASYARAKAT MELALUI PELATIHAN PRODUK OLAHAN STIK IKAN CAKALANG (Katsuwonus pelamis) DI DESA BULUWATU KECAMATAN SUMALATA TIMUR - Erlansyah Erlan; Abdurahman Kano Mohamad (Madani: Jurnal Pengabdian Ilmiah, 2023)
Buluwatu Village, which is located in East Sumalata District, is a village located in the coastal area of ​​North Gorontalo Regency, which has fishery and marine resources that have the potential to be developed. Through this community service, we empower the community in training activities for processed skipjack fish sticks (Katsuwonus pelamis) to support community income. This community service aims to assist the community through training on processed Cakalang fish stick products. This community service activity uses training methods with participatory learning techniques and direct practice of processing Cakalang fish into fish sticks. The result of this community service activity is the creation of processed Cakalang fish sticks, which have a savory taste and high nutritional content and are well-liked by both children and adults. Keywords: Buluwatu Village; Fish Sticks; Processed Fishery Products.